An Investigation On Construction Sequence Of Irregular Multi-Layer Prism Tensegrity - Low, Zhao Xuan (Universiti Sains Malaysia, 2018)
Tensegrity structures are structures where its compression members (struts) are connected by continuous tension members (cables). The structure shows its rigidity through the self-equilibrium between the struts and the cables with the introduction of pre-stress. The construction of tensegrity structures is challenging due to its high sensitivity where its shape is unstable during construction. However, studies or literature on construction sequence of full scale tensegrity structures is relatively lacking. Hence, the study on application of form-finding results to the eventual construction of a tensegrity considering practical issues is needed. The focus of this study is irregular multi-layer prism tensegrity. A computational tool which uses a linear approach by combining length relation condition and force equilibrium equation is used in the form-finding process. The pre-stressing forces in the cables are applied based on the elongation of the cables. The construction sequence is investigated and improved through the erection of physical models. The effect of the construction sequence on the final configuration of the multi-layer prism tensegrity is studied. A detailed construction sequence of multi-layer prism tensegrity is proposed.